Menertawakan Fobia Komunis di Era Reproduksi Digital - Triyono Lukmantoro (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Abstract. In May-June 2016 issue of the rise of the Indonesian Communist Party (PKI) and the latent danger of communism appeared again. Excessive fear of PKI and communism continues propagated. That is what is referred to as a communist phobia. But, the issue is considered sensitive that it gave birth to criticism. The phenomenon is the presence of a number of memes comics whose contents laugh hammer and sickle symbol and three communist iconic figures, namely D.N. Aidit, Tan Malaka, and Mao Zedong. Meme comics containing parody to show incongruities that can only happen to the era of digital reproduction. The idea of meme comics can be traced to the thought Walter Benjamin about the works of art in the age of mechanical reproduction. In that era, aura was declining. The crisis and the disappearance of aura increasingly occurs to the time of digital reproduction.